A research investigation to identify the key players in the two-stroke engine industry - Wahla, N.
The paper illustrates the key players in this industry from both R&D and production viewpoints, as well as the location of individual sites for the manufacture of two-stroke engines.
Engines which produce power by the two-stroke combustion principle are manufactured in considerable quantities in major industrial centres throughout the world. This paper describes part of a research investigation examining the two-stroke engine industry and the markets into which these products are sold. The publication brings together commercial and technical information which is intended to contribute towards a better understanding of a sector of manufacturing engineering which is part of the supply chain for the transportation and power generation industry. The paper focuses on the key players in the two-stroke combustion engine industry, from both the research and development and production points of view, and identifies the geographical location of individual sites. The overall aim of the research investigation is to be able to build a mix of expertise, including technical, commercial and marketing knowledge, related to two-stroke engines, which is valuable to those who are interested in powered transport methods. The results presented include some basic statistics of the number and spread of the key players and active sites whilst beginning to develop an understanding of the drawbacks and advantages and complementary specialisms which make up the two-stroke engine technology.
Keywords: Engine industry